Subgroup analysis of Japanese patients in a Phase 3 study of atezolizumab in advanced triple-negative breast cancer (IMpassion130). (15th October 2019) - Iwata, Hiroji; Inoue, Kenichi; Kaneko, Koji; Ito, Yoshinori; Tsugawa, Koichiro; Hasegawa, Ayumi; Nakagawa, Shintaro; Kuratomi, Hiroyasu; Tamura, Kenji
Abstract: Background: In the randomised Phase 3 IMpassion130 trial, atezolizumab combined with nab-paclitaxel (atezo + nab-P) in 902 patients with triple-negative breast cancer (TNBC) showed prolonged progression-free survival (PFS) in both the intention-to-treat (ITT) population and programmed death-ligand 1 (PD-L1)–positive subgroup compared with placebo plus nab-P (plac + nab-P). This study assessed the efficacy and safety of atezo + nab-P in the IMpassion130 Japanese subpopulation. Methods: Eligible patients had unresectable locally advanced or metastatic TNBC previously untreated with chemotherapy for metastatic disease. Patients were randomised 1:1 to receive either atezo + nab-P or plac + nab-P. Co-primary endpoints were investigator-assessed PFS and overall survival (ITT population and PD-L1–positive subgroup). These were also assessed in the Japanese subpopulation. Results: There were 65 Japanese patients (34 atezo + nab-P; 31 plac + nab-P). The PD-L1–positive subgroup included 25 patients (12 atezo + nab-P; 13 plac + nab-P). Median PFS was 7.4 months (atezo + nab-P) versus 4.6 months (plac + nab-P; hazard ratio [HR], 0.47; 95% CI, 0.25–0.90). In the PD-L1–positive subgroup, median PFS was 10.8 months (atezo + nab-P) versus 3.8 months (plac + nab-P; HR, 0.04; 95% CI, <0.01–0.35). Safety results in the Japanese subgroup were consistent with those in the overall population. The Japanese subgroup had a lower incidence of adverse events leading to treatment withdrawal than the overall population. More patients in the atezo + nab-P arm had neutrophil count decreases and stomatitis than patients in the plac + nab-P arm. Conclusions: Atezo + nab-P efficacy in Japanese patients was consistent with the overall IMpassion130 population. No new safety signals were observed, and tolerability was consistent with that of the overall population. Abstract : The efficacy of atezolizumab plus nab-paclitaxel in Japanese patients with triple-negative breast cancer was consistent with the overall IMpassion130 population. No new safety signals were observed.